A Study on the Influence of TV Cartoon Programs on Children (International Journal of Innovative Research in Engineering & Management, 2021)
Children's cartoons are the most popular kind of entertainment. In  recent years, children have gotten considerably extra interested in  cartoons, as well as it has becomes their main leisure. Children  often begin viewing cartoons on television when they are six  months old and become devoted viewers by the age of two or  three. Children's interest in cartoons has expanded dramatically  over time, and it has become a popular pastime in some homes.  This study is conducted using a questionnaire survey.  Respondents came from a variety of schools and different parts of  Delhi. Survey research is one of the most important domains of  measurement in applied social research. The interviews, which  included open-ended questions, focused on children's behavior.  An online survey was used to analyze the data, which was  completed via online forms. A total of 100 people from various  parts of Delhi were asked to participate in the research by filling  out questionnaires. Children's behavior was significantly  influenced by watching cartoons and there were both bad and  good changes. The majority of children respond in the same  manner they do when they watch adults conduct things on  television and emulate them in their daily lives. The future scope  of this study is to spread awareness about the major impacts of  the Watching TV cartoons program on children’s and how to save  the children’s from its bad impacts.
Keywords: Cartoon Characters; Cartoon; Children; Entertainments; Television